دراسة النمو الإعاشي وتشكيل بداءات الأجسام الثمرية للفطر Lentinus tigrinus على أوساط مختلفة في الزجاج - يازجي ميساء (Latakia University Journal -Biological Sciences Series, 2019)
اختبرت قدرة الفطر الدعامي (Bull. ex Fr.) Fr. Lentinus tigrinus على النمو الإعاشي وتشكيل بداءات الأجسام الثمرية وتطورها، وذلك على أربعة أوساط مغذية مختلفة Sabouarud , M.E. A, P.D.A) ,Lima bean) في المختبر. بينت النتائج قدرة الفطر المدروس على النمو إعاشياً على جميع الأوساط، وإعطاء مشائج قطنية بيضاء اللون وكثيفة جداً غطت كامل سطح طبق البتري 9cm بعد 7 أيام من الزراعة في الزجاج عند الدرجة 25 م°. شكل الفطر كميات كبيرة من بداءات الأجسام الثمرية مع تطور بسيط للقبعات، دون الوصول إلى مرحلة النضج الكامل للجسم الثمري بعد 15 يوماً من الزراعة ، وذلك على الوسطين P.D.A وM. E. A فقط بينما كان النمو إعاشياً فقط على الوسطين Sabouraud وLima bean. أظهرت الدراسة النسيجية للبداءات الثمرية تشكل الوصلات الكلابية التي تعد الخلايا الأساسية لتكوين الثمار الفطرية والدعامات عند الفطريات الدعامية. The capacity of Fungus Lentinus tigrinus (Bull. ex Fr.) Fr. on the Vegetativ growth and formation of primordia fruiting bodies, and their development were tested on four different media in the labs. The results showed the capacity of L. tigrinus on the vegetative growth on all media and giving cottony thickly white colour mycelium and cover all the surface of all the plate 9 cm after 7 days of culturing at 25C°. The fungi formed enormous quantity of primordia fruiting bodies with simply development of pileus, without reaching to complet ripe period after 15 days of cultured on two media P.D.A and M.E. A only. While the vegetative growth was only on the two media Sabouraud and Lima bean. The Tissue Study of primordia demonstrated the formation of clamp connections which are Consider essential cells for carpogenesis and Basidia at Basidiomycetes.